2020
DOI: 10.14715/cmb/2020.66.3.4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-92b as a marker for TPF induced chemotherapy response prediction and prognosis evaluation in with advanced oral squamous cell carcinoma patients

Abstract: This study aimed to explore the clinical value of miR-92b in advanced oral squamous cell carcinoma (OSCC) and to observe the relationship between miR-92b and TPF induced chemotherapy and prognosis. Totally 114 patients with advanced OSCC admitted to our hospital were selected as the study subjects, all of whom received docetaxel, cisplatin and 5-fluorouracil (TPF) induction chemotherapy. In addition, another 80 healthy subjects who underwent physical examination in our hospital from the same period were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Therefore, the prognosis of TPF is worth studying. microRNA-92b is a marker for predicting the response to TPF induction chemotherapy and evaluating the prognosis of patients with advanced OSCC [30]. In addition, in our previous studies, the expression of stromal cell derived factor-1 and nerve growth factor (NGF) was up-regulated in the tumor stage of TNM, while NGF protected salivary glands from radiotherapy damage [31].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the prognosis of TPF is worth studying. microRNA-92b is a marker for predicting the response to TPF induction chemotherapy and evaluating the prognosis of patients with advanced OSCC [30]. In addition, in our previous studies, the expression of stromal cell derived factor-1 and nerve growth factor (NGF) was up-regulated in the tumor stage of TNM, while NGF protected salivary glands from radiotherapy damage [31].…”
Section: Discussionmentioning
confidence: 95%
“…Although some studies have shown that miR-92b may be related to the proliferation and chemotherapy response of oral squamous cell carcinoma (OSCC) [ 22 , 23 ], its specific biological role and molecular mechanism in the invasion and migration of HNSCC are still unclear. In this regard, we hypothesized that miR-92b plays an important role in the development of HNSCC, and studied whether transcription factor SP1 promotes the invasion and migration of head and neck squamous cell carcinoma cells through the interaction with miR-92b, supporting a novel feed-forward loop with a significantly important role in the progression of HNSCC.…”
Section: Introductionmentioning
confidence: 99%